Analisis Pada Perusahaan PT Kereta Cepat Indonesia China (WHOOSH) - Amelia Sandyrani; Eli Jamilah Mihardja (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study explores the condition of PT Kereta Cepat Indonesia China (KCIC), a company in a paradoxical situation: enjoying public popularity for its role in modern transport development while simultaneously facing major financial and operational challenges. A descriptive qualitative approach was employed using Miles and Huberman's inductive analysis method, combined with GE-McKinsey and SWOT frameworks. Data were collected through document review, secondary literature analysis, and triangulation from multiple sources. The study identifies distress indicators such as cost overruns, operational delays, and foreign loan dependency. KCIC's adaptation strategies include financial restructuring, operational optimization, and multi-stakeholder collaboration. Additional strategies are also proposed, such as funding diversification, technological innovation, sustainability efforts, and enhanced local community engagement. The success of the Jakarta–Bandung High-Speed Rail project relies heavily on the effective execution of strategies, stakeholder support, and adaptability to changing conditions.